DISKRIPSI DAN MANFAAT TANAMAN OBAT DI PEDESAAN SEBAGAI UPAYA PEMBERDAYAAN APOTIK HIDUP (STUDI KASUS DI KECAMATAN WONOKERTO) - Pudjiati Syarif; Bambang Suryotomo(; Hayati Soeprapto (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
This  research  aims  to  identify  and  know  the  benefits  of  herbs  at  the  village  as  a  source  of traditional medicine and find the villages which have high potential to reserve herbal garden. The methodology of the research is a survey with proporsiv random sampling at Wonokerto, Pekalongan district. The sample of the research is 30 % of 11 villages as the population. They are  Wonokerto  Kulon,  Api-Api,  Pesanggrahan,  and  Sijambe.  The  result  of  the  research indicates that at the location of the research, there are 40 species of herbs which can be used as  a  source  of  traditional  medicine.  This  herbal  can  be  used  to  cure  the  diseases,  such  as: itchy, inflamed, tuberculosis, flu, kidney, diabetic, liver, maag, rheumatic, reducing fat, high tension, heart disease, cancer, and etc. But the utilization of herbs as traditional medicine has not been used by the villagers. The herbs are mostly found in Sijambe village, it means that this village has good potential to develop herbal garden.Key words: Herbal Garden, herbs.